333 Comparison of Carinata Meal and Canola Meal with or without Wheat Dried Distiller's Grains with Solubles on Rumen Fermentation, Omasal Nutrient Flow, Microbial Protein Synthesis and Total Tract Digestibility. (7th December 2018) - Guidotti, E; Penner, G; Christensen, D; Yu, P; McKinnon, J
Abstract: This study evaluated carinata (CRM) versus canola meal (CM) fed alone or in combination with wheat-dried distillers' grains with solubles (WDDGS) as a protein supplement for beef cattle. The trial was designed as a Latin square with 4 rumen-cannulated heifers (386 ± 27.95 kg; mean ± SD) fed a barley-based backgrounding (BK) diet with CRM (9.2% DM); CM (10.0% DM); CRM (5.0% DM) + WDDGS (5.3 DM); or CM (5.0% DM) + WDDGS (5.3 DM) as protein sources. Rumen and omasal samples were collected every 8 h for 3 d. Fecal output was collected every 2 h for 5 days. Omasal digesta flow and nutrient digestibility were measured with the triple marker technique using chromium-EDTA, ytterbium chloride and indigestible NDF. Microbial protein synthesis was determined using nitrogen labelled ammonium sulphate. Ruminal pH, ammonia, acetate, propionate and butyrate concentrations were not affected ( P > 0.05) by treatment. No treatment differences were detected for omasal nutrient flow or apparent digestion of DM, OM or NDF, as well as for true ruminal OM digestion. Apparent digestion of N tended ( P = 0.09) to be greater for CRM and CM diets relative to WDDGS diets (-10.0 ± 2.73 vs. 13.9 ± 14.81 g d -1 ). The inclusion of WDDGS increased ( P = 0.04) N truly digested in the rumen (154.5 ± 0.16 vs. 177.9 ± 0.55 g d -1 ), and decreased (228.0 ± 2.45 vs. 205.6 ± 20.07 g d -1 ) ruminal non-ammonia nitrogen (NAN) flow. No treatment differences (P > 0.05) were noted in total bacterial NAN flow or in microbial efficiency. Total tract nutrient digestibility was not ( P > 0.05) affected by treatment. These results indicate that CRM, relative to CM, does not affect rumen fermentation, nutrient utilization and microbial protein synthesis with no benefit to adding WDDGS as a rumen undegradable protein source.